Enhancing the efficiency of polymerase chain reaction using graphene nanoflakes - Khaliq R., Abdul; Kafafy, Raed Ismail; Salleh, Hamzah Mohd.; Faris, Waleed Fekry (Institute of Physics Publishing, 2012)
The effect of the recently developed graphene nanoflakes (GNFs) on the polymerase chain reaction (PCR) has been investigated in this paper. The rationale behind the use of GNFs is their unique physical and thermal properties. Experiments show that GNFs can enhance the thermal conductivity of base fluids and results also revealed that GNFs are a potential enhancer of PCR efficiency; moreover, the PCR enhancements are strongly dependent on GNF concentration. It was found that GNFs yield DNA product equivalent to positive control with up to 65% reduction in the PCR cycles. It was also observed that the PCR yield is dependent on the GNF size, wherein the surface area increases and augments thermal conductivity. Computational fluid dynamics (CFD) simulations were performed to analyze the heat transfer through the PCR tube model in the presence and absence of GNFs. The results suggest that the superior thermal conductivity effect of GNFs may be the main cause of the PCR enhancement.